The Social Cost of Carbon and the Ramsey Rule. - Cees A. Withagen (Center for Economic Studies and ifo Institute (CESifo), 2018)
The objective of this paper is to critically assess the use simple rules for the social cost of carbon (SCC) employing a rudimentary form of the Ramsey rule. Two interrelated caveats apply. First, if climate change poses a serious problem, it is hard to justify an exogenous constant growth rate of consumption. Second, to derive the SCC one needs full knowledge of the entire future. Popular assumptions to get around this, such as assuming current GDP is optimal, are difficult to justify.
Keywords: Q54; 330